An analysis of China's biomass briquette fuel large‐scale steam heating system. (24th June 2022) - Zhang, Runkai; Wang, Yapeng; Sun, Yufeng; Wang, Zhanwu; Gao, Jing; Guo, HaiQin; Cheng, Shangshang; Xu, Guanghui; Li, Baoqian; Xu, Guangyin
Abstract: The current study took Henan Wufeng New Energy Science Technology Co. Ltd as an example to investigate a large‐scale steam heating system with biomass briquette fuel in Henan, China. Drawn on several months of field research, the economic cost and greenhouse gas emissions for peanut shell straw collection, transportation, storage and burning at Henan Wufeng New Energy Science Technology Co. Ltd were analyzed in 2021. Moreover, the economic cost and greenhouse gas emissions were used as evaluation indicators to evaluate the biomass molding fuel supply system systemically. Economic analysis shows that the steam heating system can make a profit of 1.72 × 10 6 yuan per year, and the input–output ratio (ROI) is 93.87%, which is much higher than the benchmark input–output ratio (30%). The very high ROI indicates that the system is difficult to operate in an economically feasible manner. Greenhouse gas emission analysis demonstrates that at the same heating level, the system can save 4.42 × 10 7  kg of standard coal and reduce the emissions of greenhouse gases to the environment by 1.25 × 10 5 tCO2eq, which has significant environmental benefits. Taken together, the government should adopt effective economic policies to promote the efficient use of biomass straw and support biomass straw recycling and heating enterprises. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd.